The Quantum Flag Manifold SUq(3)/T2 as an Example of a Noncommutative Sphere Bundle - Tomasz Brzezinski (arXiv, 2019)
The quantum flag manifold ${SU_q(3)/\T^2}$ is interpreted as a noncommtative bundle over the quantum complex projective plane with the quantum or Podle\'s sphere as a fibre. A connection arising from the (associated) quantum principal $U_q(2)$-bundle is described.